Arterial spectral waveform analysis in the prediction of diabetic foot ulcer healing. (October 2021) - Normahani, Pasha; Agrawal, Rishi; Sounderajah, Viknesh; Tsinaslanidis, Prodromos; Musonda, Patrick; Mehar, Zaheer; Powezka, Katarzyna; Bravis, Vasiliki; Aslam, Mohammed; Jaffer, Usman
Objective: We assessed the association between (1) severity of vessel wall calcification, (2) number of patent vessels at the ankle and (3) arterial spectral waveform features, as assessed on a focused ankle Duplex ultrasound (DUS), and healing at 12-months in a cohort of patients who had their diabetic foot ulcers conservatively managed. Research design and methods: Scans performed on 50 limbs in 48 patients were included for analysis. Patient health records were prospectively reviewed for 12-months to assess for the outcome of ulcer healing. Results: We identified that the number of waveform components, peak systolic velocity, systolic rise time and long forward flow as well as the number of vessels patent at the ankle on DUS, may be useful independent predictors of healing, as noted by the trend towards statistical significance. Conclusion: Arterial spectral waveform features may be useful in predicting the chance of diabetic foot ulcer healing.